DESAIN MODEL BASIS DATA OBYEK PARIWISATA PROVINSI JAWA TENGAH STUDI KASUS DI KABUPATEN MAGELANG - Wasino Wasino; Jap Tji Beng; Desi Arisandi (Jurnal Informatika, 2016)
Magelang District is implementing the tourism development program that consists of: marketing development, tourism destination development, partnership development, and tourism infrastructure development. Data about tourism in Magelang regency has not been stored correctly according to the rules of database normalization, with redudancy data storage, including the data that stored and informed online. A good information system should be supported by accurate data and stored on a database that has been normalized, so that data can be read by the system or a different program with different goals and views. Based on the analysis of data obtained in Magelang District, there are several the same ways and the same and the different way of storing and displaying information tourism objects. Normalization process conduct on the obtained data until the 3rd normal form to eliminate the partial dependencies and transitive dependencies. The result of the reseach is a database model.